Baicalein alleviates fibrosis and inflammation in systemic sclerosis by regulating B-cell abnormalities - Bo Peng; Qin Hu; Rong He; Hongping Hou; Dongyin Lian; Ying Chen; Han Li; Ling Song; Yunhang Gao; Tengfei Chen; Guangping Zhang; Jianrong Li (BMC, 2023)
Abstract Background Systemic sclerosis (SSc; also known as "scleroderma") is an autoimmune disorder characterized by extensive fibrosis, vascular changes, and immunologic dysregulation. Baicalein (phenolic flavonoid derived from Scutellaria baicalensis Georgi) has been used to treat the pathological processes of various fibrotic and inflammatory diseases. In this study, we investigated the effect of baicalein on the major pathologic characteristics of SSc: fibrosis, B-cell abnormalities, and inflammation. Methods The effect of baicalein on collagen accumulation and expression of fibrogenic markers in human dermal fibroblasts were analyzed. SSc mice were produced by injecting bleomycin and treated with baicalein (25, 50, or 100 mg/kg). The antifibrotic features of baicalein and its mechanisms were investigated by histologic examination, hydroxyproline assay, enzyme-linked immunosorbent assay, western blotting and flow cytometry. Results Baicalein (5-120 μM) significantly inhibited the accumulation of the extracellular matrix and fibroblast activation in transforming growth factor (TGF)-β1- and platelet derived growth factor (PDGF)-induced human dermal fibroblasts, as evidenced by abrogated deposition of total collagen, decreased secretion of soluble collagen, reduced collagen contraction capability and downregulation of various fibrogenesis molecules. In a bleomycin-induced model of dermal fibrosis in mice, baicalein (25-100 mg/kg) restored dermal architecture, ameliorated inflammatory infiltrates, and attenuated dermal thickness and collagen accumulation in a dose-dependent manner. According to flow cytometry, baicalein reduced the proportion of B cells (B220+ lymphocytes) and increased the proportion of memory B cells (B220+CD27+ lymphocytes) in the spleens of bleomycin-induced mice. Baicalein treatment potently attenuated serum levels of cytokines (interleukin (IL)-1β, IL-2, IL-4, IL-6, IL-17A, tumor necrosis factor-α), chemokines (monocyte chemoattractant protein-1, macrophage inflammatory protein-1 beta) and autoantibodies (anti-scleroderma 70 (Scl-70), anti-polymyositis-scleroderma (PM-Scl), anti-centromeres, anti-double stranded DNA (dsDNA). In addition, baicalein treatment can significantly inhibit the activation of TGF-β1 signaling in dermal fibroblasts and bleomycin-induce mice of SSc, evidenced by reducing the expression of TGF-β1 and IL-11, as well as inhibiting both small mother against decapentaplegic homolog 3 (SMAD3) and extracellular signal-related kinase (ERK) activation. Conclusions These findings suggest that baicalein has therapeutic potential against SSc, exerting modulating B-cell abnormalities, anti-inflammatory effects, and antifibrosis.